Fagopyrum esculentum ssp. ancestrale-A Hybrid Species Between Diploid F. cymosum and F. esculentum - Cheng, Cheng; Fan, Yu; Tang, Yu; Zhang, Kaixuan; Joshi, Dinesh C.; Jha, Rintu; Janovská, Dagmar; Meglič, Vladimir; Yan, Mingli; Zhou, Meiliang (Frontiers in Plant Science, 2020)
Fagopyrum cymosum is considered as most probable wild ancestor of cultivated buckwheat. However, the evolutionary route from F. cymosum to F. esculentum remains to be deciphered. We hypothesized that a hybrid species exists in natural habitats between diploid F. cymosum and F. esculentum. The aim of this research was to determine the phylogenetic position of F. esculentum ssp. ancestrale and to provide new thoughts on buckwheat evolution. Different methodologies including evaluation of morphological traits, determination of secondary metabolites, fluorescence in situ hybridization (FISH), comparative chloroplast genomics, and molecular markers were deployed to determine the phylogenetic relationship of F. esculentum ssp. ancestrale with F. cymosum and F. esculentum. The ambiguity observed in morphological pattern of genetic variation in three species revealed that F.esculentum ssp. ancestrale is closely related to F. cymosum and F. esculentum. Flavonoid analysis revealed that F.esculentum ssp. ancestrale is closely related to F. esculentum. Comparative chloroplast genome analysis further supported the close proximity of F. esculentum ssp. ancestrale with F. esculentum. Additionally, molecular marker analysis revealed that F. esculentum ssp. ancestrale exhibits co-dominance with the bands amplified by F. cymosum and F. esculentum. These finding provided supporting evidence in favor of the hypothesis that F. esculentum ssp. ancestrale is a hybrid species between F. cymosum to F. esculentum, which was probably originated by spontaneous hybridization under natural conditions.